2019
DOI: 10.3389/fpls.2019.00159
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Performance of Rice Genotypes for Improving Yield and Adaptability Under Direct Seeded Aerobic Cultivation Conditions

Abstract: With the changing climatic conditions and reducing labor-water availability, the potential contribution of aerobic rice varieties and cultivation system to develop a sustainable rice based agri-food system has never been more important than today. Keeping in mind the goal of identifying high-yielding aerobic rice varieties for wider adaptation, a set of aerobic rice breeding lines were developed and evaluated for grain yield, plant height, and days to 50% flowering in 23 experiments conducted across different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Recently, a GWAS on complex mapping population revealed co-location of QTLs for root traits with nal1, OsIPT3 and EL5, OsNAR2.1 genes for root development and nitrate uptake, respectively (Sandhu et al, 2019a). Also, many significant and stable QTLs influencing panicle architecture (Deshmukh et al, 2010;Guo and Hong, 2010;Okada et al, 2018;Sun et al, 2017) and root structure (Arai-Sanoh et al, 2014;Sandhu et al, 2013Sandhu et al, , 2015Sandhu et al, , 2019aUga et al, 2013) are reported and being used for developing DDSRsuited varieties (Sandhu et al, 2019b).…”
Section: Grain Yield Under Water-deficit Conditionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, a GWAS on complex mapping population revealed co-location of QTLs for root traits with nal1, OsIPT3 and EL5, OsNAR2.1 genes for root development and nitrate uptake, respectively (Sandhu et al, 2019a). Also, many significant and stable QTLs influencing panicle architecture (Deshmukh et al, 2010;Guo and Hong, 2010;Okada et al, 2018;Sun et al, 2017) and root structure (Arai-Sanoh et al, 2014;Sandhu et al, 2013Sandhu et al, , 2015Sandhu et al, , 2019aUga et al, 2013) are reported and being used for developing DDSRsuited varieties (Sandhu et al, 2019b).…”
Section: Grain Yield Under Water-deficit Conditionmentioning
confidence: 99%
“…Root trait QTLs, qNR 4.1 , qNR 5.1 (nodal root number) and qRHD 1.1 , qRHD 5.1 , qRHD 8.1 (root hair density), for higher nutrient availability under dry direct‐seeded conditions, qEVV 9.1 , qEVV 9.2 (early vegetative vigour), qEMM 1.1 (early uniform emergence), qGY 1.1 , qGY 8.1 , qGY 10.1 (grain yield) and qLDG 4.1 (lodging resistance) along with QTLs/genes for biotic resistance ( Gm4, Bph3, Bph17, Pi9, Pita2, Xa4, xa5, xa13, Xa21 ) and major drought QTLs ( qDTY 1.1 , qDTY 2.1 , qDTY 3.1 and qDTY 12.1 ) were pyramided through MAS (Sandhu et al ., 2019b). Single plant selection strategy for grain yield under DDSR condition along with genotyping for targeted QTLs/genes was performed from F 1 to F 6 generations to achieve homozygosity.…”
Section: Genomic Breeding For Developing Ddsr Varietiesmentioning
confidence: 99%
See 2 more Smart Citations
“…These two statistical methods (AMMI and GGEBiplot) have wider importance for agricultural researchers because they affect to any two-way data matrices (Farhad et al, 2017;Crossa, 1990). AMMI analysis can also be used to find out the stability of the genotypes across locations using the PCA (principal component axis) scores and AMMI stability value (Sandhu et al, 2019;Purchase, 1997). Research on adaptability of the Aus rice varieties would help farmers to cultivate right varieties in right environments as well as the policy makers to formulate decision in this regard.…”
Section: Introductionmentioning
confidence: 99%